Chusquea nedjaquithii (Poaceae: Bambusoideae, Bambuseae, Chusqueinae), a new endemic species from Oaxaca, Mexico - Ruiz-Sanchez, Eduardo; Mejía-Saulés, Teresa; Clark, Lynn G. (Phytotaxa, 2014)
Chusquea is the most diverse among woody bamboo genera, with 174 described species. Not surprisingly, Chusquea is the most diverse bamboo genus in Mexico, and with the description of C. nedjaquithii the number of species will increase to 20, representing almost 45% of the total Mexican woody bamboo diversity. Based on fieldwork in the Mexican state of Oaxaca and revision of herbarium specimens we describe and illustrate C. nedjaquithii, a species endemic to the Sierra Madre del Sur in Oaxaca, Mexico. Chusquea nedjaquithii is similar to C. liebmannii but differs in having culms with deciduous hairs, an oblate central bud and fewer subsidiary buds, strongly geniculate branches in one row forming an incomplete verticil, oblique foliage leaf blade bases, and longer inner ligules in the foliage leaves. A key to the Mexican Chusquea species based on vegetative characters is provided.